Kesenjangan Modal Budaya dan Adaptasi Ekonomi: Analisis Partisipasi Generasi Muda dan Integrasi Digital di Cianjur Selatan - Sumarhaeti, Hehet (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of cultural capital-based creative economy on the economic adaptation of the community in Southern Cianjur, examining the mediating role of youth participation and the moderating effect of digital integration. Utilizing a quantitative explanatory approach, data were collected through questionnaires from 105 respondents who are local creative economy actors. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The research findings reveal that cultural capital has a positive and highly significant influence on driving youth participation. This indicates that local wisdom is an effective symbolic asset for fostering youth agency in rural areas. However, the results also show that neither cultural capital nor youth participation has a significant impact on actual community economic adaptation. Furthermore, digital integration has not been able to strengthen the relationship between these variables toward economic resilience. This discrepancy indicates a bottleneck in transforming the spirit of cultural preservation into structured economic independence. This study concludes that strengthening creative economy capacity in rural areas requires more integrative policies, focusing not only on cultural identity and technological support but also on restructuring supply chains and market innovation to achieve sustainable transformational adaptation.